Accuracy assessment of kinematic PPP versus PPK for GNSS flights data processing - Gurturk, Mert; Soycan, Metin (TAYLOR & FRANCIS LTD, 2022)
The integration of survey-grade Global Navigation Satellite Systems (GNSS) with photogrammetric measurement studies conducted with an aircraft has the potential to meet the need for the use of ground control points (GCP). In photogrammetric studies, there are different GNSS techniques to provide the precise positioning of the aircraft. The precise point positioning (PPP) technique has become an alternative method to post-processing kinematic (PPK) methods in the evaluation of GNSS data gathered with an aircraft at high speed. In this study, GNSS data gathered from two different flights conducted for photogrammetric surveys in Izmir, Turkey were processed with different software (RTKLIB, gLAB, CSRS-PPP, and GRAFNAV) through PPP technique with the ambiguity resolution (PPP-AR) method to analyse the performance of this method versus PPK. Three-dimensional (3D) positioning analyses of coordinate differences obtained from mapping flights demonstrated a variation pattern mainly between 0 and 6 cm for both kinematic PPP and PPK results.
Keywords: GNSS; PPP-AR; PPK; Photogrammetric Flight; Accuracy; Engineering; Geology; Remote Sensing